Evaluation of the Impact of Irradiance Lamps and Storage Media on Elution of TEGDMA from Dental Composites - Tauseef, Kiran; Amin, Faiza; Moin, Syed Faraz; Khurshid, Zohaib; Aslam, Kashif; Jabeen, Bushra (European Journal of Dentistry, 2024)
Objectives The aim of this study was to evaluate and compare the effect of irradiance light and storage media on the elution of triethylene glycol dimethacrylate (TEGDMA) from conventional Filtek Z350XT 3M ESPE and two bulk-fill composites Shofu Beautifil-Bulk and Filtek Bulk fill flowable 3M ESPE using high-performance liquid chromatography (HPLC).Materials and Methods Shofu Beautifil-Bulk, Filtek Bulk fill flowable 3M ESPE, and Filtek Z350XT 3M ESPE were the three types of composites used in this study. Disk shaped samples of 4-mm thickness and 10-mm diameter were fabricated using a stainless steel mold and were polymerized using light emitting diode (LED) and quartz tungsten halogen (QTH) lamps. After polymerization, the samples were immersed in ethanol, artificial saliva with betel quid extract, and distilled water for 1, 7, and 30 days, respectively. The elution of monomer TEGDMA was evaluated using HPLC.Statistical Analysis To evaluate the mean concentration difference, mixed way analysis of variance (ANOVA) was applied. Between different light, materials, and within the time duration, Tukey's post hoc test was used. A p value of 0.05 was considered significant.Results During the first day of storage, a significant amount of monomer TEGDMA elution was seen in all the materials. The highest values observed to be in the disks cured with QTH lamp. However, the highest elution was seen when the disks were immersed in ethanol/water solution. While the most stable medium was distilled water, artificial saliva with betel nut extract also had a significant effect on the elution of TEGDMA. The highest value obtained was of Filtek Bulk fill flowable 3M ESPE after 30 days of immersion in both LED and QTH cured disks.Conclusion Filtek Bulk fill flowable 3M ESPE shows better properties in relation to the release of monomer TEGDMA as it releases less amount of monomer in the storage media. The release of monomer was highest in ethanol as compared to artificial saliva and distilled water with the passage of time.
Keywords: degree of conversion; light curing units; dental composites; elution of monomer; high-performance liquid chromatography